KEDUDUKAN HAK PAKAI SEBAGAI OBYEK HAK TANGGUNGAN - Hadi Putra, Yosep (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
The Article 51 of Law No. 5 of 1960 on the Basic Agrarian Law states decisivelythat only property right, right to use and the right to use a building that can beused as collateral for debt with burden of mortgage. In principle, the object ofmortgages is the right to land that complete the requirements which is must beregistered (to qualify for publicity) and it can be proclaimed (to facilitate theimplementation of debt payments guaranteed repayment). In the other hand, thedepelopment of credit currently provides the possibility related to the right usedas an object of mortgage and it strengthened by Law No. 4 of 1996 on the Rightsof the land and items related to land although it is not explicitly regulated in theUUPA.Keywords: use right as mortgage object